Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening: Studi Pada Prusahaan Manufaktur Sub Sektor Otomotif dan Komponen yang Terdaftar di BEI Periode 2016-2021 - Riahman Damanik, Erdy; Purnamasari, Atika (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To test the effect of profitability and leverage on company value with dividend policy as an intervening variable in automotive and component companies listed on the Indonesian Stock Exchange in 2016-2021. Background Problems: he increasing number of new manufacturing companies emerging in Indonesia in various fields, resulting in increasingly tight competition between business actors. Novelty: Retesting the same variables by previous researchers by adding intervening variables. Research Methods: This study uses a type of hypothesis testing or causal research using secondary data on 6 Companies and the data analysis technique used is multiple linear regression with the help of the SPSS 25 program. Findings/Results: Profitability does not have a significant effect on company value through dividend policy, leverage has a significant effect on company value through dividend policy, simultaneously profitability and leverage have a significant effect on company value through dividend policy.. Conclusion: Company dividends are stored in the form of retained earnings so that they can be useful for financing future company investments and use retained earnings as business capital so that companies maximize internal capital, reduce debt as external capital